A model for the formation of stellar associations and clusters from giant molecular clouds - Grudić, Michael Y.; Kruijssen, Diederik; Faucher-Giguère, Claude-André; Hopkins, Philip F; Ma, Xiangcheng; Quataert, Eliot; Boylan-Kolchin, Michael (Monthly notices of the Royal Astronomical Society, 2021)
We present a large suite of magnetohydrodynamic simulations of turbulent, star-forming giant molecular clouds (GMCs) with stellar feedback, extending previous work by simulating 10 different random realizations for each point in the parameter space of cloud mass and size. It is found that once the clouds disperse due to stellar feedback, both self-gravitating star clusters and unbound stars generally remain, which arise from the same underlying continuum of substructured stellar density, i.e. the hierarchical cluster formation scenario. The fraction of stars that are born within gravitationally bound star clusters is related to the overall cloud star formation efficiency set by stellar feedback, but has significant scatter due to stochastic variations in the small-scale details of the star-forming gas flow. We use our numerical results to calibrate a model for mapping the bulk properties (mass, size, and metallicity) of self-gravitating GMCs on to the star cluster populations they form, expressed statistically in terms of cloud-level distributions. Synthesizing cluster catalogues from an observed GMC catalogue in M83, we find that this model predicts initial star cluster masses and sizes that are in good agreement with observations, using only standard IMF and stellar evolution models as inputs for feedback. Within our model, the ratio of the strength of gravity to stellar feedback is the key parameter setting the masses of star clusters, and of the various feedback channels direct stellar radiation (photon momentum and photoionization) is the most important on GMC scales.
Gesehen am 22.10.2021